TEACHERS' PERSPECTIVE ON TEACHING ASSISTANCE PROGRAM OF MERDEKA BELAJAR KAMPUS MERDEKA AT SMKN 1 TIDORE - Badrun, Fitriana; Ismail, Anwar; Ismail, Ade (Jurnal Bilingual, 2023)
This research aims to explore and analyse teachers’ perspectives on the teaching assistance program of Merdeka Belajar - Kampus Merdeka at SMK Negeri 1 Tidore Kepulauan. The research used qualitative method with questionnaire as the primer data and interview as the secondary data. The researcher selected three English teachers at SMKN 1 Tidore Kepulauan to involve in this research as a respondent. As a result, Teaching assistants in the MBKM program, supports school teachers with their English lessons. In addition, teaching assistants can adapt to the school and class environment and student behaviour within the class. When a manager gives him an opinion, he supports it. Second, teaching assistants also use learning media that appeal to the classroom, such as electronic media that are highly relevant today. In addition, we use several teaching strategies that can increase students' interest in learning and solve classroom teaching problems. They usually use games to boost the mood of their students while learning English. Finally, in order to grasp the student's learning progress, the teaching assistant will administer the test as an evaluation form and the test result will be evaluated by the teaching assistant. Therefore, the deficiencies in their teaching to students can be identified.